2017
DOI: 10.12816/0038190
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Serum Amyloid A Level in Pregnancies Complicated with Preterm Premature Rupture of Membranes

Abstract: Background: serum amyloid A (SAA) is a cytokine-inducible acute-phase reactant whose plasma concentrations can exceed 1 mg/mL during an acute-phase response (500 to 1000 fold of plasma levels greater than in the non inflammatory state) thus representing an ideal marker for clinical use. Preterm premature rupture of membranes (PPROM) complicates only 2% of pregnancies but is associated with 40% of preterm deliveries and can result in significant neonatal morbidity (Prematurity, sepsis and pulmonary hypoplasia) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…The results of the meta-analysis based on the p-value functions of each study are displayed in a drapery plot (p-value on the y-axis and the effect size on the x-axis) (Figure 3). [22][23][24][25][26].…”
Section: Results Of Synthesesmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of the meta-analysis based on the p-value functions of each study are displayed in a drapery plot (p-value on the y-axis and the effect size on the x-axis) (Figure 3). [22][23][24][25][26].…”
Section: Results Of Synthesesmentioning
confidence: 99%
“…These results suggest that these biomarkers could potentially be useful in predicting preterm birth. Moreover, in the study by ElShourbagy et al (2017), we found that amyloid has an increased risk for PPROM but has a low predictive value [ 26 ]. However, the low predictive value of amyloid also raises questions about its usefulness as a standalone diagnostic tool.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations